Developing Kopaja.id as a fun online learning in general tax conditions topic - Rumiyati Rumiyati; Dianila Oktyawati (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
Kopaja.id as online learning had developed in 2019, and KOPAJA is an acronym for